Reddit post summarization based subreddit analysis - Ng, Jesline (Nanyang Technological University, 2023)
Social media has merged seamlessly into modern-day civilization and has now become a necessary component of daily life. With the large amount of post and information available, social media consumers were often overwhelmed and left confused. To overcome this issue, the responses to the social media were analyzed. The project focused on a social media platform called Reddit. The project intended to create a web application that gathers and analyzes comments using a combination of existing web design and analysis techniques. This analytical data was presented in a straightforward web interface to help users comprehend the public’s viewpoints.